The Bacterial Type III Secretion System as a Broadly Applied Protein Delivery Tool in Biological Sciences - Liyu Jia; Lihua Zhu (Microorganisms)
The type III secretion system (T3SS) is a nano-machine that allows Gram-negative bacteria to alter eukaryotic host biology by directly delivering effector proteins from the bacterial cytoplasm. Protein delivery based on the bacterial T3SS has been widely used in research in biology. This review explores recent advancements in the structure and function of the T3SS. We explore the molecular underpinnings of the T3SS apparatus, which spans bacterial and host cell membranes, and discuss the intricate transport mechanisms of effector proteins. Furthermore, this review emphasizes the innovative applications of the T3SS in crop biology, where it has been leveraged to study plant–pathogen interactions. By summarizing the current knowledge and recent progress, we underscore the potential of the T3SS as a powerful tool in biological sciences and their implications for future research in plant pathology and agricultural biotechnology.